2014
DOI: 10.1039/c3nr05348b
|View full text |Cite
|
Sign up to set email alerts
|

Flexible transparent conducting composite films using a monolithically embedded AgNW electrode with robust performance stability

Abstract: We report on the performance of an all-in-one flexible hybrid conducting film employing a monolithically embedded AgNW transparent electrode and a high-performance glass-fabric reinforced composite substrate (AgNW-GFRHybrimer film). Specifically, we perform in-depth investigations on the stability of the AgNW-GFRHybrimer film against heat, thermal oxidation, and wet chemicals to demonstrate the potential of the hybrid conducting film as a robust electrode platform for thin-film optoelectronic devices. With the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 26 publications
3
85
0
Order By: Relevance
“…It has been reported that the morphology of AgNW changed a lot after high-energy sintering, of which nanoparticles or knurls can be observed within several hours. [ 27 ] The similar change was also detected in pristine AgNW after treatment by chloride ions at room temperature, as shown in Figure 6 a. Nanoparticles on the surface of Ag nanowire were observed in the SEM image during the early storage in air. At last the whole Ag nanowires were fully corroded to lose their initial shape, and only vary-shaped particles were left.…”
Section: Resultssupporting
confidence: 64%
“…It has been reported that the morphology of AgNW changed a lot after high-energy sintering, of which nanoparticles or knurls can be observed within several hours. [ 27 ] The similar change was also detected in pristine AgNW after treatment by chloride ions at room temperature, as shown in Figure 6 a. Nanoparticles on the surface of Ag nanowire were observed in the SEM image during the early storage in air. At last the whole Ag nanowires were fully corroded to lose their initial shape, and only vary-shaped particles were left.…”
Section: Resultssupporting
confidence: 64%
“…Several issues, however, still need to be addressed before AgNW networks can be widely applied in electronic devices. First, strong adhesion between the AgNW network and substrate needs to be achieved, as the AgNW network is easily detached from the substrate . Second, the AgNW network cannot be used as‐prepared, but heat treatment at around 200 °C is first required in order to obtain the high electrical conductivity of AgNW‐based TCEs.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that a bottom-embedded metal NW network is effectively protected from oxidation by a top ITO overcoating layer. 24,26,39 The chemical stability of the metal NW TCEs is another important issue because many device fabrication processes involve chemicals that could degrade the bottom metal NW network. To determine the chemical stability of c-ITO/metal NW-GFRHybrimer films, K 2 S corrosion tests were performed.…”
Section: Mechanical Thermal and Chemical Robustness Of Metal Oxide/mmentioning
confidence: 99%
“…22,23 In particular, the thermal/chemical instability of metal NW TCEs is the most critical drawback for this material's use in viable optoelectronic devices that require high-temperature annealing and various chemical treatments during the device fabrication. 24,25 Conductive metal oxide/metal NW composite TCEs would be beneficial in terms of their thermal/chemical stability because most metal oxides are thermodynamically stable. 26,27 However, two inevitable disadvantages accompany the introduction of metal oxides: (1) a degradation of the optoelectrical performance 28,29 and (2) a reduction in mechanical flexibility.…”
Section: Introductionmentioning
confidence: 99%